Differences in absconding between African and European honeybee subspecies facilitate invasion success of small hive beetles - (:unkn) unknown (My University, 2018)
AbstractSmall hive beetle (SHB) is an invasive species in populations of European honeybee subspecies, but underlying reasons for SHB success are not well understood. African and European honeybee, Apis mellifera, subspecies differ in absconding, and small hive beetle, greater wax moth (GWM) and ants all can exploit abandoned nests. However, the impact of host absconding on SHB reproduction and the role of GWM and ants as competitors are not known. Here, we conducted a survey in South Africa, Australia and the USA to evaluate SHB and GWM reproduction and foraging by ants in abandoned honeybee colonies. While the impact of competing ants and GWM was not significant, the data show higher SHB reproduction in abandoned nests of European honeybees compared to African ones, but less for GWM. The positive correlation between abandoned protein sources (brood, pollen) on SHB reproduction suggests that the less efficient preparation for absconding by European honeybee subspecies combined with their large colony sizes is a key factor for the invasion success of SHB.
Keywords: African Research